GPU Optimization Techniques Applied to Scale Free Gene Regulatory Networks Based on Threshold Function - Jacob, Vinícius Vilar; Ferreira, Chaulio de Resende; Ferreira, Ricardo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2012: Anais do XIII Simpósio em Sistemas Computacionais de Alto Desempenho, 2012)
This paper describes the use of GPU-specific optimization techniques applied to the problem of simulation of scale free gene regulatory networks based on threshold function on GPU. We made attempts to optimize memory access, change the data structure used to represent the graph, use of stream and ILP (Instruction Level Parallelism) on the implementation made in an earlier work by Campos et al (2011). The optimizations that showed more effectiveness were the change in the representation of the graph, ILP and stream with speedup up to 5.99 times over the previous approach which was also done on GPU.